Tayangan Video Animasi “Si Nopal” Untuk Mendukung Interaksi Sosial Siswa Sekolah Dasar - Ghafiruna Al Aziz; Chumi Zahroul Fitriyah; Zetti Finali (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2020)
Social interaction is a dynamic social relationship that involves relationships between individuals, between groups, and between individuals and groups. The purpose of this research is to analyse an animated film